Synthesis and Properties of Novel Polyazobenzene - Li, Weiwei; Xu, Dongmei (Asian Journal of Chemistry, 2013)
A novel aromatic polyazo compound 1,2-bis[4-((4,6-bis((4-phenyl diazenyl)phenoxy)-1,3,5- triazin-2-yl)oxy)phenyl]diazene with five azobenzene units was facilely constructed by dehydrochlorination reaction between p-hydroxyazobenzene, 4,4'-dihydroxyazobenzene and cyanuric chloride under very mild conditions. Compared to azobenzene, the crystallinity of polyazo compound with five azobenzene units greatly decreased, while the thermostability remarkably improved. The maximal absorption wavelength of polyazo compound with five azobenzene units was close to that of azobenzene, but the molar extinction coefficient of polyazo compound with five azobenzene units was near five times of that of azobenzene. Polyazo compound with five azobenzene units exhibited typical reversible photoisomerization behaviours and was expected to be applied in photonic material areas.